Domestic and Sexual Violence and Abuse: Tackling the Health and Mental Health Effects - Itzin, Catherine; Taket, Ann; Barter-Godfrey, Sarah (Routledge, 2010)
Domestic violence, childhood sexual abuse, rape and sexual assault, and sexual exploitation through prostitution, pornography and trafficking can have many significant adverse impacts on a survivor’s health and wellbeing, in the short, medium and long-term. Taking a life-course approach, the book explores what is known about appropriate treatment responses to those who have experienced, and those who perpetrate, domestic and sexual violence and abuse. The book also examines key factors that are important in understanding how and why different groups experience heightened risks of domestic and sexual violence and abuse, namely: gender and sexuality; race and culture; disability; and abuse by professionals. Drawing together results from specially commissioned research, the views of experts by experience, experts by profession and the published research literature, the book argues that sufficient is already known to delineate an appropriate public health framework, encompassing primary, secondary and tertiary prevention, to successfully tackle the important public health issue represented by domestic and sexual violence and abuse. Domestic and Sexual Violence and Abuse equips health and social care professionals and services to identify and respond to the needs of affected individuals with a view to the prevention and early intervention.
Keywords: FAMILY & RELATIONSHIPS; Family & Relationships / Abuse / Child Abuse; Family & Relationships / Abuse / General; Health & Fitness / Women's Health; Medical / Allied Health Services / General; Medical / Health Care Delivery; Psychology / Mental Health; Social Science / Sexual Abuse & Harassment; Social Science / Social Work; Social Science / Violence in Society

Music Education in the 21st Century in the United Kingdom: Achievements, Analysis and Aspirations - Hallam, Susan; Creech, Andrea Ed (Institute of Education - London, 2010)
The landscape of music education in the UK is constantly shifting and developing. This book provides a timely and unique overview of this restless sector by considering the achievements of music education, analysing its current performance and setting out aspirations for the future. "Music Education in the 21st Century in the United Kingdom" addresses the power of music to influence and change human behaviour, analyses current and future issues in music education and casts a spotlight on particular areas of education, including early years, the primary school, the secondary school, further education, universities and conservatoires, music services, the music studio and the role of music leaders and community musicians. Written by experts in the field of music education, the book provides an authoritative account of the current status of music education in the UK. While essential to understand the current and future context in the UK, the book will be invaluable to those involved in music education internationally, as it includes chapters on the provision of music education for all children, listening, the role of singing, playing an instrument, creativity, the role of technology, issues of performance and assessment, learning through the lifespan and the initial and ongoing education of music teachers. It also includes a range of case study examples and evaluations of practice. The book is a landmark publication in the field of music education and will be essential reading for policy-makers, practitioners, music students, trainee music teachers and those who provide music services in the UK and internationally. This book contains three parts. Part I, "Introduction", contains: (1) The power of music: its impact on the intellectual, personal and social development of children and young people (Susan Hallam); and (2) Contextualising music education in the UK (Pauline Adams, Hilary McQueen, and Susan Hallam). Part 2, "Current Issues in Music Education", contains: (3) Music for all (Graham Welch and Adam Ockelford); (4) Listening (Susan Hallam); (5) The role of singing (Jo Saunders, Maria Varvarigou and Graham Welch); (6) Learning to play an instrument (Susan Hallam and Andrea Creech); (7) Creativity (Susan Hallam and Lynne Rogers); (8) The role of technology (Evangelos Himonides and Ross Purves); (9) Issues of assessment and performance (Ioulia Papageorgi and Susan Hallam); (10) Learning through life (Hilary McQueen and Maria Varvarigou); and (11) The initial and ongoing education of music teachers (Colin Durrant and Kate Laurence). Part 3, "Contexts of Learning", contains: (12) Music in the early years (Andrea Creech and Jessica Ellison); (13) Music in the primary school (Jessica Ellison and Andrea Creech); (14) Music in the secondary school (Hilary McQueen and Susan Hallam); (15) Music in further education colleges (John Conlon and Lynne Rogers); (16) Music in universities and conservatoires (Helena Gaunt and Ioulia Papageorgi); (17) Music Services (Lynne Rogers and Susan Hallam); (18) The music studio (Andrea Creech); (19) The role of music leaders and community musicians (Andrea Creech); and (20) Where now? (Susan Hallam and Andrea Creech). This book also contains: Acknowledgements; Preface; Notes on contributors; and Index.
Keywords: Adult Education; Creativity; Early Childhood Education; Educational Trends; Elementary Education; Evaluation; Foreign Countries; Futures (of Society); Higher Education; Individual Development; Inservice Teacher Education; Intellectual Development; Leaders; Lifelong Learning; Listening; Music Education; Music Teachers; Musical Instruments; Musicians; Performance; Preservice Teacher Education; Secondary Education; Singing; Social Development; Technology Uses in Education

“Yes, I Do but Not with You”: Qualitative Analyses of Sexual/romantic Overture-Related Aggression in Bars and Clubs - Graham, Kathryn; Wells, Samantha; Bernards, Sharon; Dennison, Susan (Contemporary Drug Problems, 2010)
Assaultive and aggressive behaviors related to sexual overtures are common in commercial drinking establishments (bars, pubs, and clubs). In this article, we examined the thematic content of 251 incidents of verbal and physical aggression related to sexual/romantic overtures documented by researcher-observers in a study of Toronto bars and clubs. Aggression was examined as it emerged in the following stages of the social interaction process: (a) sexual/romantic overtures that began aggressively; (b) initiators of sexual/romantic overtures who became aggressive later in the social interaction process; (c) aggression by targets of overtures; and (d) aggression by third parties. From these thematic analyses we identify the distinctions between predatory and genuine overtures and explore the potential role of the effects of alcohol.

Comparative Gender and Institutions: Directions for Research - Chappell, Louise (Perspectives on Politics, 2010)
A comparative politics of gender offers an opportunity to consider in detail the operation of gender within political institutions. As such, it contributes to a deeper understanding of the roles and experiences of men and women within political institutions, of the policies, laws and norms that are the outcomes of these institutions, and of the relationship between these institutions and social actors. This essay proposes a multi-directional strategy for undertaking comparative gender and institutional research that includes taking account of similarities and differences within and across states, between states and international institutions, across space as well as across time. It argues that through this research strategy it is possible to gain a more nuanced understanding of gender processes and outcomes, which is valuable to those working both inside and outside political institutions to advance a women's equality agenda.